Efektivitas Pengendalian Jaringan Wi-Fi dengan Metode Evil Limiter Linux di UKM PT Bimuda Karya Teknik - Azzam Aziandani Hidayat; Johan Pamungkas; Alfa Yuliana Dewi (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Limitations in traffic management features on ISP-provided routers are a common issue in industrial Wi-Fi networks, particularly in maintaining the stability of production network connections. The absence of bandwidth control mechanisms allows non-priority devices to consume excessive bandwidth, thereby degrading the quality of operational network services. This study aims to analyze the effectiveness of Evil Limiter as a software-based bandwidth management solution by utilizing the ARP redirection mechanism without requiring administrative access to the router or modifications to the network infrastructure. The research employs an experimental approach conducted on a production Wi-Fi network at PT Bimuda Karya Teknik using three testing scenarios: baseline, limiting, and blocking. Network performance is evaluated based on Quality of Service (QoS) parameters referring to the TIPHON standard, including throughput, delay, jitter, and packet loss. The results indicate that Evil Limiter is effective in controlling traffic from non-priority devices, where in the blocking scenario, target devices are completely isolated with a throughput of 0 Mbps and a packet loss of 100%, while the limiting scenario significantly reduces internet access for non-priority devices. Overall, the proposed method is proven to improve network stability for priority devices, particularly under high network load conditions.